Aplicação do indicador OEE para melhoria de produtividade em um processo de produção contínuo - Santos, Rodinaldo Ferreira dos (Universidade do Vale do Rio dos Sinos, 2020)
With the continuous competition between companies in the quest to increase their market share in which they operate, the reduction of operating costs is the basis for remaining competitive, and for that, increasing the volume of production without increasing costs is fundamental, however, in the manufacturing processes there may be so-called bottlenecks that prevent or restrict the ability to meet demand, impacting costs. In view of this, the use of indicators is important for the company's management to make important decisions, however, large companies invest and seek to work with the correct indicators according to their manufacturing process. Based on this, the present article carries out a case study, presenting the implementation of the OEE (Overall Equipment Effectiveness) method in the bumper painting sector of a multinational company in which it has extensive experience in the management of indicators, but had difficulties in interpretation of those related to the measurement of process restrictions (bottlenecks). The implementation of OEE, was precisely with the objective of replacing the method used until then to measure yield and thereby bring assertiveness in interpretations, robust action plans and improvement in productivity. The implementation project went through the challenge of using the OEE tool in a continuous production flow and for that, it used the GPT (Workplace Management) method, adapting the tool and achieving the expected result in reducing restrictions and improving in the sector's income.
Keywords: Restrições de processos industriais; IROG – Índice de rendimento operacional global; Gestão do posto de trabalho; Industrial process restrictions; IROG – Global operating income index; Workplace management